Profound immunodeficiency with severe skin disease explained by concomitant novel CARMIL2 and PLEC1 loss-of-function mutations - Maccari, Maria E (Clinical immunology (Orlando, Fla.), 2019)
Copyright © 2019 Elsevier Inc. All rights reserved.